2020
DOI: 10.3390/ma13122806
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy Evaluation of 14 Maxillary Full Arch Implant Treatments Performed with Da Vinci Bridge: A Case Series

Abstract: The use of pterygoid implants can be an attractive alternative to sinus bone grafting in the treatment of posterior atrophic maxilla. This technique has not been widely used because of the difficulty of the surgical access, the presence of vital structures, and the prosthetic challenges. The use of dynamic computer aided implantology (DCAI) allows the clinician to utilize navigation dental implant surgery, which allows the surgeon to follow the osteotomy site and implant positioning in real time. A total of 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Figure 2 shows the complete flowchart of the study selection process. Of the 24 articles, 10 reported on clinical studies involving humans [43][44][45][46][47][48][49][50][51][52] and 14 reported on preclinical "in vitro" studies [53][54][55][56][57][58][59][60][61][62][63][64][65][66]. The types of studies included for each system can be observed in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2 shows the complete flowchart of the study selection process. Of the 24 articles, 10 reported on clinical studies involving humans [43][44][45][46][47][48][49][50][51][52] and 14 reported on preclinical "in vitro" studies [53][54][55][56][57][58][59][60][61][62][63][64][65][66]. The types of studies included for each system can be observed in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Pterygoid implants in a full-arch rehabilitation obtain an optimal distribution of functional loads thanks to a wider implant-prosthetic polygon. Apart from a case report without immediate loading [ 31 ], the use of bilateral pterygoid implants associated with two to four standard fixtures in the anterior zone, with a flapless approach, has been reported by Stefanelli et al [ 26 ] for the immediate loading full-arch rehabilitation of the upper jaw. These authors adopted the dynamic navigation implantology after a digital accurate planning to reduce the risk of anatomical injuries and to facilitate prosthetic management.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this report’s clinicians, really expert, could not have otherwise reached all their goals, a fast and harmless flapless surgical procedure with an immediate aesthetic and functional prosthetic finalization, at least with such accuracy. The ND system adopted to treat the herein reported case presents the advantage of accomplishing the registration process by tracing the existing teeth, used as fiducial markers [ 26 ]: the presence of stable residual teeth, to be removed because useless for the prosthetic rehabilitation, allows the software to overlap the planning information on the preliminary taken by the patient CBCT, avoiding the need of a new one, that generally must be performed after the insertion of the fiducial markers. This property could not have been exploited in this case report, for the stability reduction of the residual teeth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The existing discrepancies between a planned implant and an inserted implant are one of the most relevant challenges for the operators to understand if the method used for that surgery is accurate enough to guarantee the requested results [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%